Analysis of Factors Associated with Stunting Incidence in Kudus Regency - Mustiko Wibowo; Bambang Budi Raharjo; Intan Zainafree (Indonesian Journal of Global Health Research, 2026)
Stunting remains a public health problem in Indonesia, including in Kudus Regency, which recorded a prevalence of 4.56 % in 2024. This condition is influenced by various factors, both maternal and family environment. This study aims to analyze factors related to the incidence of stunting in toddlers in Kudus Regency, including a history of Chronic Energy Deficiency (CED) in pregnant women, a history of anemia, family socio-economic conditions, and feeding patterns. The study design used a case-control with a retrospective approach. The sample consisted of 200 respondents, consisting of 100 stunted toddlers (cases) and 100 non-stunted toddlers (controls) selected using consecutive sampling method in 19 community health centers in Kudus Regency. Data were collected through interviews with a structured questionnaire from the results of previous research on the history of Chronic Energy Deficiency (CED), Anemia, family socio-economics and feeding patterns and analyzed using the Chi-Square test. Bivariate analysis showed that history of CED (OR = 5.05 ; p < 0.001), history of anemia (OR = 2.12; p = 0.028), family socioeconomic status (OR = 0.14; p = 0.001), and feeding patterns (OR = 0.18; p < 0.001) were significantly associated with the incidence of stunting. The incidence of stunting in toddlers in Kudus Regency is influenced by maternal factors (CED and anemia), family socioeconomic factors, and feeding patterns, with feeding patterns being the dominant factor. Stunting prevention efforts need to focus on improving maternal nutrition, preventing anemia, empowering families economically, and educating toddlers on feeding practices.